Development planning for school improvement (School development series, 1994)
Development planning is a relatively new concept in a changing educational vocabulary. Different terms are now being used both within and between countries, and the same term does not always have a shared meaning. There is, however, something of a common core in both the origin and definition of the concept, whatever particular name is used. Development planning is a response to the need for a systematic and whole-school approach to planning and the management of multiple innovations and change. Although development planning is now a widespread innovation, its success or effectiveness in terms of school improvement is by no means established. The relative youth of development planning as a school improvement strategy, and the fact the research is set within specific national or local contexts, means that far less is known than anyone cares to admit